Icariside Ⅱ Attenuates Palmitic Acid-Induced Endothelial Dysfunction Through SRPK1-Akt-eNOS Signaling Pathway - Gu, Yang-Yang; Tan, Xiao-Hui; Song, Wen-Peng; Song, Wei-Dong; Yuan, Yi-Ming; Xin, Zhong-Cheng; Wang, Jia-Dong; Fang, Dong; Guan, Rui-Li (Frontiers in Pharmacology, 2022)
Background: Endothelial dysfunction is commonly accompanied by a reduced capacity for nitric oxide (NO) production and decreased NO sensitivity, playing a central role in numerous vascular diseases. Saturated free fatty acids are known to reduce NO production and then induce endothelial dysfunction. Alternative splicing plays a key role in the regulation of cellular and tissular homeostasis and is highly regulated by serine-arginine protein kinase (SRPK1). The role of SRPK1 in the biology of endothelial cells remains elusive. Icariside Ⅱ (ICA Ⅱ) has been reported to have protective effects on endothelial function. However, the specific molecular mechanisms are still unknown. The purpose of this study is to explore the role of SRPK1 in the biology of endothelial cells and the underlying mechanism of the protective effect of ICA Ⅱ on palmitic acid (PA) induced endothelial dysfunction. Methods: Endothelial dysfunction model was constructed using PA in human umbilical vein endothelial cells (HUVECs). The expression and phosphorylation of related proteins in the SRPK1-Akt-eNOS signaling pathway were detected by Western Blot. Cell Counting Kit-8 assay and Ki67 immunofluorescence were used to estimate cell viability. Endothelial cell function was assessed by detecting NO production using DAF-FM DA. Interaction between ICA Ⅱ and SRPK1 was demonstrated by a biotinylated protein interaction pull-down assay. Results: The expressions of eNOS, Akt, and SRPK1 were down-regulated in the endothelial dysfunction stimulated by PA. SRPK1 inhibitor SPHINX31 restrained endothelial cell viability in a dose-dependent manner. Moreover, inhibition of SRPK1 using SPHINX31 and knockdown of SRPK1 by shRNA also showed a down-regulation of the expression of the proteins associated with the SRPK1-Akt-eNOS signaling pathway. Biotinylated protein interaction pull-down assay revealed that ICA Ⅱ could be directly bound with SRPK1. On the other hand, ICA Ⅱ could attenuate the PA-induced endothelial dysfunction and restore cell viability through the SRPK1-Akt-eNOS pathway. Conclusions: ICA Ⅱ, bound with SRPK1, could attenuate the endothelial dysfunction induced by PA in HUVECs via the SRPK1-Akt-eNOS signaling pathway.